2010 Fifth International Conference on Software Engineering Advances 2010
DOI: 10.1109/icsea.2010.66
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Distributed Development in Students' Global Software Development Projects: The Role of Agile Methodologies and End-to-End Tooling

Abstract: From 2005 to 2008, we explored different models of collaboration in student software development projects. In the past, project roles were distributed across students in the US, Cambodia, India and Thailand. What was common to our previous models was the co-location of developers, the client and quality assurance roles being the ones that were commonly distributed. A loose waterfall software development process was always used and activities were supported by a mashup of technologies. In 2009, we distributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In the previous instance of our course, we found that the Scrum method, along with supporting collaboration practices and tools, supports the learning of important GSE competencies, such as distributed communication and teamwork, building and maintaining trust, using appropriate collaboration tools, and inter-cultural collaboration [7]. Scharff et al [4]- [6] found that Scrum increased the transparency of both the process and the developed software product in their GSE course using Scum practices over three years after transitioning from teaching the course using the waterfall methodology.…”
Section: B Teaching Gsementioning
confidence: 67%
See 1 more Smart Citation
“…In the previous instance of our course, we found that the Scrum method, along with supporting collaboration practices and tools, supports the learning of important GSE competencies, such as distributed communication and teamwork, building and maintaining trust, using appropriate collaboration tools, and inter-cultural collaboration [7]. Scharff et al [4]- [6] found that Scrum increased the transparency of both the process and the developed software product in their GSE course using Scum practices over three years after transitioning from teaching the course using the waterfall methodology.…”
Section: B Teaching Gsementioning
confidence: 67%
“…In line with this shift in industry trends, examples of software engineering curricula teaching GSE using agile methods have emerged [4]- [7]. The reported courses are practical, project-driven, utilize agile development methods like Scrum [8] and are arranged in collaboration between two or more universities, enabling students to learn GSE in realistic settings [9].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges were cultural differences, timezone differences, technical difficulties and the differences in semesters and courses between two universities as reported in [4]. In [5], there is a case study of a team that developed a Target First Grade project that is a mobile application for children learning mathematics, reading geography and writing. This project took nine weeks to develop.…”
Section: Related Workmentioning
confidence: 99%
“…Transitioning to Distributed Development in Students' Global Software Development Projects [5] The results of this paper are limited as it depends on two projects only and it selected interview method for collecting data. There were challenges with coordination in both projects when applied SoS meetings.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation